2002
DOI: 10.1097/00005650-200203000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Differences in Sociodemographic Determinants of Breast Conserving Treatment Despite Overall Increased Adoption

Abstract: Sociodemographic differences in BCT use have persisted over time. The increased overall adoption of BCT has not led to consistency in use of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
82
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 34 publications
5
82
1
Order By: Relevance
“…Furthermore, it is difficult for patients with low incomes to afford the expense of radiotherapy following breast-conserving surgery. In addition, these patients usually live in areas in which it may be difficult to obtain radiotherapy (Gilligan et al, 2002). Our research did not find any influence of education level on surgical treatment options, which may reflect the small numbers of breast cancer cases in this study or the large number of patients with unidentified education backgrounds that were included.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, it is difficult for patients with low incomes to afford the expense of radiotherapy following breast-conserving surgery. In addition, these patients usually live in areas in which it may be difficult to obtain radiotherapy (Gilligan et al, 2002). Our research did not find any influence of education level on surgical treatment options, which may reflect the small numbers of breast cancer cases in this study or the large number of patients with unidentified education backgrounds that were included.…”
Section: Discussionmentioning
confidence: 63%
“…This may be because patients with low-income and high-stress occupations delay in presenting at clinic and are therefore more likely to present with advanced stages of breast tumors (Grunfeld et al, 2002;Bish et al, 2005), thus losing the opportunity for sentinel lymph node biopsy and breast-conserving surgery. In contrast, patients in higher income occupations are more likely to accept new concepts and technologies, thus leading to their increased acceptance of sentinel lymph node biopsy and breast-conserving surgery (Gilligan et al, 2002;Keating et al, 2003). Furthermore, it is difficult for patients with low incomes to afford the expense of radiotherapy following breast-conserving surgery.…”
Section: Discussionmentioning
confidence: 99%
“…First, we developed and validated an algorithm to identify incident breast cancer cases [9] and validated the endpoint analyzed with a random sample of medical records. Second, the study is population-based and minimize selection bias of predictors of cancer treatment such as geographic, regional, urban vs. rural location, and socioeconomic status [29]. Third, we were able to adjust for several important covariates, both at the patient and healthcare system levels.…”
Section: Discussionmentioning
confidence: 99%
“…10 The most recent study from 1996 found that less than half of elderly breast cancer patients undergo BCT with or without radiation. 11 Reasons for the underuse of BCT in the elderly are unclear. Low use of BCT has been correlated with rural healthcare settings, [11][12][13][14] treatment received in the southern and central United States, 12,15 and low patient socioeconomic status.…”
mentioning
confidence: 99%
“…11 Reasons for the underuse of BCT in the elderly are unclear. Low use of BCT has been correlated with rural healthcare settings, [11][12][13][14] treatment received in the southern and central United States, 12,15 and low patient socioeconomic status. 11,16 The influence of these nonclinical factors on the surgical treatment of breast cancer suggests that informed patient choice may not be fully optimized in this population.…”
mentioning
confidence: 99%